Relationship between body sway and body build in healthy adult men and women - Lipowicz, Anna; Bugdol, Monika N.; Graja, Katarzyna; Nowakowska-Lipiec, Katarzyna; Jochymczyk-Woźniak, Katarzyna; Fryc, Dobrochna; Michnik, Robert; Mitas, Andrzej W. (Anthropological Review, 2023)
Studies investigating the relationship between balance ability and body size, build and proportions tend to concentrate on body mass and height rather than breadth parameters or size of individual body segments. The purpose of this study was to determine a relationship between the ability to keep balance and the size, build and proportions, based on breadth and length dimensions of the body in healthy adult men and women during a position of free standing. This study also aimed to investigate how the lack of visual control affects the analyzed relationship. The study group consisted of 102 adults of both sexes. The investigations encompassed anthropometric measurements of the body and the ability to keep balance. The analysis covered a of series anthropometric parameters, 9 indices of body proportions, mean velocity of the COP movement (MV) and ellipse area (EA). A statistical analysis of the results was carried out taking into consideration the division into groups due to sexes. The results of the Pearson correlation have revealed that there is a statistically significant correlation (weak or moderate degree) between anthropometric parameters of the body and stabilographic values. Results differ between sexes and depend on whether Romberg’s test was performed with open or closed eyes. The obtained results showed that the surface area of ellipse significantly depends on the dimensions of these body elements which relate to the position of the centre of mass. The obtained results, which differ depending on sex, show that the values of the body sways in a position of free standing depend on breadth and length dimensions of the body, visual control and the analyzed parameter of balance.